The levels of glutathione peroxidase, vitamin A, E, C and lipid peroxidation in patients with transitional cell carcinoma of the bladder - Yalçin, O; Karatas, F; Erulas, FA; Özdemir, E (Wiley, 2004)
To assess the levels of erythrocyte glutathione peroxidase (GSH-Px), and the serum levels of antioxidant vitamins (A, E and C), selenium and malondialdehyde (MDA) in patients with transitional cell carcinoma (TCC) of the bladder. The study comprised 91 people (23 healthy controls and 68 patients with TCC). Erythrocyte GSH-Px activity was measured by spectrophotometry, high-performance liquid chromatography to detect serum levels of vitamins and MDA, and fluorometry to detect serum levels of selenium. The serum levels of vitamin A, E and C, and selenium were significantly lower (P < 0.05) in patients with TCC than in controls. However, erythrocyte GSH-Px activities (P < 0.05) and serum MDA levels (P < 0.01) were significantly higher in patients with TCC than in the controls. Levels of free oxygen species were higher, and antioxidant vitamin and selenium levels lower, in patients with bladder TCC than in controls. These findings, with the results of previous animal studies, suggest that giving vitamin A, C, E and selenium may be beneficial in preventing and treating human bladder cancer.
Keywords: TCC; malondialdehyde; glutathione peroxidase; selenium; vitamin A, C, E